The Bangladesh Midwifery Programme a giant step towards Safe Motherhood - Ahmed, Tahera (Bangladesh Journal of Bioethics, 2015)
Safe Motherhood is not only a Reproductive Right but also a basic human right. Provision of Safe Motherhood services like skilled attendants at birth reduces maternal deaths and morbidities. Bangladesh has reduced maternal deaths from 540/ 100,000 live births in the nineties to 194 in 2010. In a recent estimate by WHO, UNICEF, UNFPA, the World Bank and the United Nations Population Division, the Maternal Mortality Rate (MMR) has declined to 170 per 100,000 live births in Bangladesh. DOI: http://dx.doi.org/10.3329/bioethics.v5i3.21535 Bangladesh Journal of Bioethics 2014; 5(3):26-27